APLIKASI PUPUK HAYATI BAKTERI ENDOFITIK TERHADAP POPULASI BAKTERI ENDOFITIK, SERAPAN N DAN BOBOT KERING TANAMAN PADI (Oryza Sativa L.) PADA TANAH SALIN - Utami, Deswita; Setiawati, Mieke Rochimi (Jurusan Agroekoteknologi Fakultas Pertanian Untirta, 2017)
Productivity of rice crops (Oryza sativa) which grown in saline soils can improve due to application endophytic bacteria biofertilizer. Endophytic bacteria lives in plant tissues have an able to fix nitrogen from the air that for supply N to plant tissue more optimal. The research was aimed to know the effects of endophytic bacteria biofertilizer on enhance bacterial populations, nitrogen uptake, and dry weight of rice grown in saline soil. This research was conducted from March 2016 until February 2017 in Soil Biology Laboratory and in Laboratory of Soil Chemistry and Fertility, Soil Science Department and Land Resources, Faculty of Agriculture, Universitas Padjadjaran and Experiment Field of Ciparanje, Faculty of Agriculture, Universitas Padjadjaran with 752 meters above the sea level. This research used Randomized Completely Block Design which consisted of eight combinations: A (salinity of 0 dS m-1), B (salinity of 0 dS m-1 + biofertilizer), C (salinity of 2 dS m-1), D (salinity of 2 dS m-1 + biofertilizer), E (salinity of 4 dS m-1), F (salinity of 4 dS m-1 + biofertilizer), G (salinity of 6 dS m-1), H (salinity of 6 dS m-1 + biofertilizer). The result showed that at salinity 2 dS m-1 rice plant still survive growing on salinity stress. Salinity treatment of 2 dS m-1 + endophytic biofertilizer have enhance affect to bacterial population, N uptake and dry weight of rice compared to salinity of 4 and 6 dS m-1.Keywords: Endophytic bacteria, Rice (Oryza sativa L.), Saline soils